2020
DOI: 10.3390/ijms21124375
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Secretome and the Surfaceome: A Strategy to Decipher the Crosstalk between Adipose Tissue and Muscle during Fetal Growth

Abstract: Crosstalk between adipose and muscular tissues is hypothesized to regulate the number of muscular and adipose cells during fetal growth, with post-natal consequences on lean and fat masses. Such crosstalk largely remains, however, to be described. We hypothesized that a characterization of the proteomes of adipose and muscular tissues from bovine fetuses may enhance the understanding of the crosstalk between these tissues through the prediction of their secretomes and surfaceomes. Proteomic experiments have id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 88 publications
(145 reference statements)
0
4
0
Order By: Relevance
“…1g). These results indicated that even as few as 1x10 6 MAs were sufficient to affect both the proliferation and the myogenic differentiation of MMCs.…”
Section: Mature Adipocytes Influence the Growth Of Mononucleated Musc...mentioning
confidence: 78%
See 1 more Smart Citation
“…1g). These results indicated that even as few as 1x10 6 MAs were sufficient to affect both the proliferation and the myogenic differentiation of MMCs.…”
Section: Mature Adipocytes Influence the Growth Of Mononucleated Musc...mentioning
confidence: 78%
“…The interaction between adipose and muscle tissues has been highlighted in numerous studies in mammals and competition between the growth of both tissues has been reported [1][2][3][4][5][6] . In the postembryonic stage, an increase in adipose tissue mass has a negative effect on muscle mass 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between adipose and muscle tissues has been highlighted in numerous studies in mammals and competition between the growth of both tissues has been reported 1 6 . For example, in mouse post-embryonic stage, an increase in adipose tissue mass has a negative effect on muscle mass 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The myokine's secretome contains many cytokines that act on various tissues, such as adipose tissue, liver, pancreas, and brain [12][13][14][15]. Among them, irisin is a novel myokine produced by the release of the proteolytically cleaved extracellular portion of the fibronectin type III domain-containing protein 5 (FNDC5) [16].…”
Section: Introductionmentioning
confidence: 99%